Analysis Of Interest Rate Through Credit Channel And The Amount Of The Money Circulation On Indonesian Economic Growth 2005 – 2019 - Afdol, Al; Mardiana, Mardiana; Widayatsar, Any (Jurnal Keuangan dan Perbankan (KEBAN), 2022)
The purpose of this study was to analyze the relationship between Interest Rates Through Credit Channels and the Money Supply on Indonesia's Economic Growth. The data used in this study is time series data from 2005 to 2019, sourced from Bank Indonesia (BI) and the Central Statistics Agency (BPS). The analytical method used in this study is Vector Autoregression (VAR) using the Eviews version 10.0 computer application program. The results show that interest rates have a negative and significant effect on lending in the short term, lending as a variable connecting interest rates has a positive and significant effect on economic growth, both in the short and long term. The banking credit variable has a significant effect on the money supply in the long term, while the money supply in both the short and long term has a negative effect on economic growth. The results of the Granger causality test show that there is a one-way causal relationship between interest rates and bank credit in Indonesia, interest rates with economic growth if we use 10% and a one-way relationship between bank credit and the money supply.